''Principled'' personalized medicine?. (November 2009) - Knoppers, Bartha Maria; Avard, Denise
The advent of both population genomic studies and direct-to-consumer personal genetic testing raises ethical challenges for researchers and physicians alike. Quality and solidarity can now be added to traditional ethical principles, such as autonomy and privacy. There is no doubt that genetic information is going ''public''. Informatic technologies allow for greater accessibility and integration, but can researchers and physicians handle the challenges? Are ethics committees equipped to handle this shift towards greater openness and towards a conflation of research and traditional medical ethics?